Public Relations Opportunities for Nurul Jadid Vocational School Through The Utilization of Virtual Community - Nuruz Zakiya; Aliwafa Aliwafa (Journal of Educational Management Research, 2022)
This study aims to illustrate that Nurul Jadid Vocational School utilizes Virtual Community in marketing educational products, in order to make it easier for the community to be able to access every activity carried out by Nurul Jadid Vocational School Students every day in Islamic boarding schools. This research uses a qualitative case study type approach, in this case the researcher wants to analyze and understand about Public Relations opportunities in Nurul Jadid Vocational School through the Virtual Community. The results of his research are the opportunities for Virtual Community for Nurul Jadid Vocational School, namely as an Information Media by using the Website that has been owned by Nurul Jadid Vocational School by including all information related to Nurul Jadid Vocational School, Vision and Mission, Structural, and information about all Nurul Jadid Vocational School programs. The second is as a Communication Media as an opportunity to influence audiences and provide information through several social media that have been provided, for example the Whatsapp group which is used as a medium to provide information related to student activities, the last as Promotional media where Nurul Jadid Vocational School carries out promotions using social media development such as posting every activity on the instastory on Instgarm SMK Nurul Jadid.